HYPERTENSION AND RISK FACTORS OF CARDIOVASCULAR DISEASE IN PEOPLE FORM 25 AGO OR MORE IN THAI BINH PROVINCE (Vietnam Journal of Community Medicine, 2021)
A cross-sectional study was carried out in 2017, with the method of cluster sampling (PPS) to select30 communes/wards in 8 districts/cities in Thai Binh province. A total of 1450 adults from 25 ago ormore the results showed that:The prevalence rate of hypertension was 29.8%, of which men account for 36.5%, 22.0% higher thanthat of women (p
Keywords: Hypertension, risk factors, adults from 25 ago or more, Thai Binh province.